A Chronic Leg Ulcer Presenting With Charcot–Marie–Tooth Disease and Type 2 Diabetes: A Case Report. (March 2013) - Ren, Haitao; You, Chuangang; Han, Chunmao
Charcot–Marie–Tooth (CMT) disease is characterized by hereditary sensorimotor polyneuropathy with foot deformity, sensorineural hearing loss, moderate developmental delay, and gait disturbance. CMT presenting with type 2 diabetes and an ulcer has not been reported. This article reports a man who presented with the symptoms mentioned above and also with a leg ulcer and type 2 diabetes. He was diagnosed with CMT disease based on family history and genetic testing. A skin defect in the left leg had manifested for more than 1 year, and results of initial fasting plasma glucose revealed type 2 diabetes. The evolution of these manifestations, coupled with a slowly progressive weakness, numbness, muscular wasting, and sensory impairment, strongly suggested the co-occurrence of 3 different diseases in the same individual.